KINERJA APARATUR SIPIL NEGARA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SDM DI KABUPATEN SOPPENG - Padauleng, Andi; Fatmawati, Fatmawati; Muhiddin, Amir (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
The aim of the research is to determine the performance of the State Civil Service Agency, descriptive research type. Data collection techniques use observation, interviews and documentation methods. Data analysis using an interactive analysis model. The results of the research show that the performance of the State Civil Service Agency for Personnel and Human Resource Development in Soppeng Regency has been maximal, both from the aspect of work quality, where the skills possessed by employees in carrying out work are in accordance with their main duties and functions, the quantity aspect of work, which is seen from how efficient and productive the employee is. in carrying out their responsibilities, the aspect of timeliness is good as seen by the absence of complaints from the public which say that requests or requests for community needs are not responded to quickly, the aspect of employee effectiveness is well understood in terms of administrative procedures, and the aspect of independence of BKPSDM employees is reflected in their ability to take action. initiative and responsibility for the tasks carried out, from these five aspects there were no complaints from the community.